Special features of friction stir welding dissimilar joints - I. K. Chernykh; E. V. Vasiliev; R. V. Dylchenko; Yu. E. Zhdanova; B. K. Igisenov (Омский научный вестник)
In this article, there is some special features of obtaining dissimilar butt-welded and lap-welded joints for various material systems. The scheme for obtaining butt-welded joints of aluminum to steel with tool displacement is analyzed. The analysis of quality and structure of welds that were manufacturing using this scheme is being conducted. The transverse micro-section of obtained specimen of the weld of aluminum alloy AMG6 to stainless steel 12H18N10T of 2 mm thickness at a welding speed of 50 rpm and a transverse speed of 50 mm/min with a tool displacement of 0,2 mm to steel part are investigated. Mutual invasion of metals to a depth of 3,2 mm and steel inclusions in an aluminum alloy of up to 0,3 mm in size are observed in the weld seam.